Towards Reliable and Quantitative Surface‐Enhanced Raman Scattering (SERS): From Key Parameters to Good Analytical Practice - Bell, Steven E. J.; Charron, Gaëlle; Cortés, Emiliano; Kneipp, Janina; Chapelle, Marc Lamy; Langer, Judith; Procházka, Marek; Tran, Vi; Schlücker, Sebastian (Angewandte Chemie International Edition, 2020)
Experimental results obtained in different laboratories world‐wide by researchers using surface‐enhanced Raman scattering (SERS) can differ significantly. We, an international team of scientists with long‐standing expertise in SERS, address this issue from our perspective by presenting considerations on reliable and quantitative SERS. The central idea of this joint effort is to highlight key parameters and pitfalls that are often encountered in the literature. To that end, we provide here a series of recommendations on: a) the characterization of solid and colloidal SERS substrates by correlative electron and optical microscopy and spectroscopy, b) on the determination of the SERS enhancement factor (EF), including suitable Raman reporter/probe molecules, and finally on c) good analytical practice. We hope that both newcomers and specialists will benefit from these recommendations to increase the inter‐laboratory comparability of experimental SERS results and further establish SERS as an analytical tool. Parameters and pitfalls: Key parameters and pitfalls that are often encountered in surface‐enhanced Raman scattering (SERS) are highlighted. Good analytical practice is proposed to increase the inter‐laboratory comparability of experimental SERS results and further establish SERS as an analytical tool.